Reflexiones sobre la educación rural en el marco de la comunicación-educación (2008)
The Colombian rural life is energized by its unique forms of production, peculiar traditions, cultural forms and its special knowledge. Consequently, rural education acquires a complexity because of these and other categories, which is why the teaching-learning processtranscends the traditional school structure. This paper presents the models which have transformed this process and which are based on curriculum contents formulated from the reality of diverse rural communities. Mainly, it presents some thoughts about the aforementioned situation of communication - education, a field that tendsto the training of critical and participatory subjects; to this end, it appeals, among other things, to alternative mass media. Finally, it proposes to link these media with the educational rural process in a planned way